Fuel poverty, uncontrollable heating expenditure, and the consequences of heat cost allocation in a large housing estate of Budapest - Tóth, Bálint Zoltán; Kocsis, János Balázs (Intersections. East European Journal of Society and Politics, 2026)
Recent initiatives in the European Union aimed at reducing energy consumption in multifamily buildings have centred on implementing heat cost allocation, which facilitates charging for heating services based on consumption. Prior experiences demonstrate that heat cost allocation efficiently decreases energy use by providing prompt feedback regarding energy usage and expense. Nonetheless, its influence on fuel poverty, energy vulnerability, and heating affordability is still inadequately comprehended. The study involved implementing personal surveys and interviews with residents of large housing estates in Budapest to investigate their experiences and coping strategies related to heating expenses, comfort, and ability to influence these aspects. It also analysed how the presence or lack of consumption-based heating service billing influences various factors, including fuel poverty. The findings indicate that heat cost allocation considerably affects energy vulnerability and fuel poverty. In buildings lacking heat cost allocation, resident agency is constrained by fixed heating expenses and the heterogeneity of the residential community, resulting in postponed purchases of essential goods and heightened energy waste. While heat cost allocation reduces consumption and improves financial flexibility, its impact on fuel poverty is ambiguous, as it does not address the broader socioeconomic and energy-efficiency determinants of energy vulnerability and fuel poverty.